PENGARUH STRUKTUR MODAL, LIKUIDITAS, STRUKTUR KEPEMILIKAN DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN INDEKS LQ45 PERIODE 2017-2022 - Amalia, Eka Lailin; Anggraeni, Anggraeni (Jurnal Ilmiah Global Education, 2023)
The purpose of this study is to analyze the influence of capital structure (DER), liquidity (si Ratio), ownership structure consisting of the Managerial Ownership (KM) and institutional ownership (KI) and company size (Size) on profitability (ROA). The population used is LQ45 Index companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The method of determining the sample used in this research is pur-posive sampling according to predetermined criteria. The analysis technique used in this study is multiple linear regression analysis using SPSS-25. The test results show that the Debt to equity ratio and managerial ownership have no significant positive effect on profitability (ROA). Cash ratio and Size have a significant negative effect on profitabil-ity (ROA). Institutional ownership has a significant positive effect on profitability (ROA).